Metafisika Eksistensial menurut Martin Heidegger: Model Manusia Altruistik di Tengah Nihilisme Kehidupan Bermasyarakat Indonesia: Existential Metaphysics according to Martin Heidegger: Altruistic Human Model amidst the Nihilism of Indonesian Social Life - Pitang, Simon Pedro; Riyanto, F. X. Eko Armada; Adon, Mathias Jebaru (Undiksha, 2024)
The focus of the research lies on exploring the meaning of human existence amidst the nihilism of life through metaphysical-philosophical reflection according to Martin Heidegger's thought. For Heidegger, humans are being-with-other; human cannot be separated from other humans in the world. Heidegger proposes how being-with-other always has a nature based on sorge or care for others in everydayness. On the other hand, humans are influenced by nihilism or live in the meaninglessness that the world offers today. Humans are increasingly showing a life of complete disregard for the world and other humans which then creates selfishness in themselves. Therefore, exploring the meaning of human existence according to Heidegger's thought will find an altruistic attitude that humans can internalize and also bring meaningful life in the midst of nihilism. The method used in the research is qualitative method through literature study. This research found that Heidegger's concept of sorge or care interprets human life as being-with-others. The contribution of this research is to awaken human altruism as being-with-other and create a meaningful life through caring for others.